2018
DOI: 10.1002/etc.4299
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of mercury contamination and associated risk to piscivorous wading birds of the south central United States

Abstract: Piscivorous birds are top predators in aquatic ecosystems and are vulnerable to mercury (Hg) exposure and associated adverse health effects. In some areas of North America, the health risk posed to piscivorous birds by Hg contamination has not been characterized because concentrations of Hg in bird tissues have not been extensively monitored. When data on Hg in tissues of piscivorous birds are not available, the concentration of Hg in the blood of piscivorous birds can be estimated from the concentration of Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In aquatic systems, inorganic mercury can be converted to highly toxic and accumulative methylmercury (MeHg) that enters the food chain and results in aquatic organisms being contaminated with MeHg (Chen and Driscoll 2018). Organisms feeding near the top of aquatic food webs, like piscivorous fish and birds, can accumulate concentrations of MeHg high enough to pose a threat to their health (Scheuhammer et al 2007;Wiener 2013;Gerstle et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In aquatic systems, inorganic mercury can be converted to highly toxic and accumulative methylmercury (MeHg) that enters the food chain and results in aquatic organisms being contaminated with MeHg (Chen and Driscoll 2018). Organisms feeding near the top of aquatic food webs, like piscivorous fish and birds, can accumulate concentrations of MeHg high enough to pose a threat to their health (Scheuhammer et al 2007;Wiener 2013;Gerstle et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These regions are critical for structuring and implementing ecosystem management strategies across federal agencies, state agencies, and nongovernmental organizations that are responsible for different types of resources within the same geographic areas (McMahon et al, 2001; Omernik & Griffith, 2014). Our previous investigations demonstrated that average concentrations of MeHg in centrarchids were significantly different between 14 Level III ecoregions located in six states: Texas, Oklahoma, Arkansas, Louisiana, Mississippi, and Tennessee (Drenner et al, 2011; Gerstle et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Our study focused on the southeastern United States, defined as a 15-state area from Texas to Maryland that accounts for 33% of the land area of the continental United States (https://www.census.gov/geographies/reference-files/ 2010/geo/state-area.html; Figure 1A). Although there have been studies of Hg contamination in fish within subregions of the southeastern United States (Adams et al, 2016;Drenner et al, 2011Drenner et al, , 2013Dong et al, 2016;Gerstle et al, 2019;Glover et al, 2010;Lange et al, 1993;Sackett et al, 2009Sackett et al, , 2013Sherman & Blum, 2013;Sveinsdottir & Mason, 2005), there has not been a comprehensive analysis of spatial patterns of Hg contamination of fish across the entire southeastern United States as have been conducted in the western United States and Canada (e.g., Eagles-Smith et al, 2016a;Lepak et al, 2016), the Laurentian Great Lakes Area (e.g., Monson et al, 2011;Sandheinrich et al, 2011), and the northeastern United States (e.g, Kamman et al, 2005;Shanley et al, 2012).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, exposure to cadmium (Cd), mercury (Hg), and selenium (Se) negatively affects the body mass/condition and health of birds by reducing their growth or body weight and, consequently, it harms survival and reproductive success [ 14 , 15 ]. Hg accumulated in body tissues can adversely affect reproduction, especially in higher trophic level species, such as fish-eating birds [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%